2022
DOI: 10.1111/jcpp.13598
|View full text |Cite
|
Sign up to set email alerts
|

Research Review: The effect of school‐based suicide prevention on suicidal ideation and suicide attempts and the role of intervention and contextual factors among adolescents: a meta‐analysis and meta‐regression

Abstract: Background Globally, suicide is the fourth highest cause of adolescent mortality (Suicide: https://www.who.int/news-room/fact-sheets/detail/suicide). The effects of post‐primary school‐based suicide prevention (PSSP) on adolescent suicidal thoughts and behaviours (STBs) have not been comprehensively synthesised. We aim to estimate the population effect for PSSP interventions on adolescent STBs and explore how intervention effects vary based on intervention and contextual moderators. Methods Searches of PsycINF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
35
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 67 publications
3
35
0
2
Order By: Relevance
“…The review and meta‐analyses by Walsh et al. (2022) provide a refreshing focus on alternative and innovative forms of intervention – namely the implementation of suicide prevention strategies in school. While the findings shed light and give hope to the efficacy of such programs, it also highlights the nascency of the field and potential lack of representation of youth in our diverse school systems.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The review and meta‐analyses by Walsh et al. (2022) provide a refreshing focus on alternative and innovative forms of intervention – namely the implementation of suicide prevention strategies in school. While the findings shed light and give hope to the efficacy of such programs, it also highlights the nascency of the field and potential lack of representation of youth in our diverse school systems.…”
Section: Discussionmentioning
confidence: 99%
“…Even more promising, the authors found that such interventions targeting suicidal thoughts and behaviors were effective in reducing suicide risk when implemented as both primary, and secondary/adjunctive interventions. The authors included 12 studies spanning across close to 30 years (1991–2020), that resulted in the examination of 33,155 youth in 329 schools between the ages of 11 and 18 years (Walsh et al., 2022). Overall findings suggest that PSSR in schools can reduce suicidal ideation and suicide attempts by 13% and 34%, respectively (Walsh et al., 2022).…”
mentioning
confidence: 99%
See 3 more Smart Citations